Over-invasion in a freshwater ecosystem: newly introduced virile crayfish (Orconectes virilis) outcompete established invasive signal crayfish (Pacifastacus leniusculus). Issue 1 (2nd January 2016) - James, J.; Thomas, J.R.; Ellis, A.; Young, K.A.; England, J.; Cable, J.
Abstract: Biological invasions are a key threat to freshwater biodiversity, and identifying determinants of invasion success is a global conservation priority. The establishment of introduced species is predicted to be hindered by pre-existing, functionally similar invasive species. Over a five-year period we, however, find that in the River Lee (UK), recently introduced non-native virile crayfish ( Orconectes virilis ) increased in range and abundance, despite the presence of established alien signal crayfish ( Pacifastacus leniusculus ). In regions of sympatry, virile crayfish had a detrimental effect on signal crayfish abundance but not vice versa. Competition experiments revealed that virile crayfish were more aggressive than signal crayfish and outcompeted them for shelter. Together, these results provide early evidence for the potential over-invasion of signal crayfish by competitively dominant virile crayfish. Based on our results and the limited distribution of virile crayfish in Europe, we recommend that efforts to contain them within the Lee catchment be implemented immediately.